IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA SISWA KELAS XI SMA NEGERI 1 SINGOSARI SEMESTER GENAP TAHUN PELAJARAN 2020/2021: SMA NEGERI 1 SINGOSARI MALANG - SITI NURHASANAH (Dewan Pendidikan Bondowoso, 2021)
Limited Face-to-face Learning allows some students to study at school even with a limited time. This opportunity is an opportunity for students to have direct discussions with teachers and students because during online learning / learning from home, student discussions with teachers and colleagues are limited to gadgets only. For this reason, a learning model that can increase student activity and creativity is needed, one of which is Problem Based Learning (PBL). There are three learning outcomes (outcomes) obtained by students who are taught with PBL, namely: (1) inquiry and problem solving skills, (2) learning adult role behaviors (adult role behaviors), and (3) independent learning skills (skills independent learning). This type of research is a first-cycle class action research using a qualitative approach. The results of this study are the implementation of the Problem Based Learning learning model on basic competencies using the menus and icons contained in the software for 10th grade students of SMA Negeri 1 Singosari in the even semester of the 2020/2021 academic year running smoothly and in accordance with the PBL learning syntax although there are some obstacles.